Identification of Mycobacterium tuberculosis in Clinical Specimens of Patients Suspected of Having Extrapulmonary Tuberculosis by Application of Nested PCR on Five Different Genes - Khosravi, Azar D.; Alami, Ameneh; Meghdadi, Hossein; Hosseini, Atta A. (Frontiers in Cellular and Infection Microbiology, 2017)
Definitive and rapid diagnosis of extrapulmonary tuberculosis (EPTB) is challenging since conventional techniques have limitations due to the paucibacillary nature of the disease. To increase the sensitivity of detection of Mycobacterium tuberculosis (MTB) in EPTB specimens, we performed a nested PCR assay targeting several genes of MTB on EPTB specimens. A total of 100 clinical specimens from suspected cases of EPTB were processed. Standard staining for acid fast bacilli (AFB) was performed as the preliminary screening test. Extracted DNAs from specimens were subjected to Nested PCR technique for the detection of five different MTB target genes of IS6110, IS1081, hsp65kd, mbp64, and mtp40. On performing AFB staining, only 13% of specimens were positive, of which ascites fluid (33.3%), followed by pleural effusion (30.8%) showed the greatest AFB positivity rate. We demonstrated slight improvement in yields in lymph node which comprised the majority of specimens in this study, by employing PCR targeted to IS6110- and hsp65-genes in comparison to AFB staining. However, the yields in ascites fluid and pleural effusion were not substantially improved by PCR, but those from bone and wound were, as in nested PCR employing either gene, the same positivity rate were obtained for ascites fluid (33.3%), while for pleural effusion specimens only IS1081 based PCR showed identical positivity rate with AFB stain (30.8%). The results for bone and wound specimens, however, demonstrated an improved yield mainly by employing IS1081 gene. Here, we report higher detection rate of EPTB in clinical specimens using five different targeted MTB genes. This nested PCR approach facilitates the comparison and the selection of the most frequently detected genes. Of course this study demonstrated the priority of IS1081 followed by mtp40 and IS6110, among the five tested genes and indicates the effectiveness of any of the three genes in the design of an efficient nested-PCR test that facilitates an early diagnosis of paucibacillary EPTB cases, which are difficult to diagnose with the available standard.